Gender bias in lupus: does immune response initiated in the gut mucosa have a role?. (29th April 2015) - Gaudreau, M.‐C.; Johnson, B. M.; Gudi, R.; Al‐Gadban, M. M.; Vasu, C.
Summary The risk of developing systemic lupus erythematosus (SLE) is approximately nine times higher among women compared to men. However, very little is understood concerning the underlying mechanisms that contribute to this gender bias. Further, whether there is a link between immune response initiated in the gut mucosa, the progression of SLE and the associated gender bias has never been investigated. In this report, we show a potential link between the immune response of the gut mucosa and SLE and the gender bias of lupus for the first time, to our knowledge. Both plasma cell‐ and gut‐imprinted‐ α4β7 T cell frequencies were significantly higher in the spleen and gut mucosa of female (SWR × NZB)F1 (SNF1) mice compared to that of their male counterparts. Importantly, female SNF1 mice not only showed profoundly higher CD45+ immune cell densities, but also carried large numbers of interleukin (IL)‐17‐, IL‐22‐ and IL‐9‐producing cells in the lamina propria (LP) compared to their male counterparts. Intestinal mucosa of female SNF1 mice expressed higher levels of a large array of proinflammatory molecules, including type 1 interferons and Toll‐like receptors 7 and 8 (TLR‐7 and TLR‐8), even before puberty. Our work, therefore, indicates that the gut immune system may play a role in the initiation and progression of disease in SLE and the associated gender bias.